What do we miss in this Orbital Retinoblastoma? Poster Presentation - Case Report - Resident - Caroline, Christella; Fedora, Ghina; Soraya, Siti Halida Zoraida; Yulia, Dian Estu (Majalah Oftalmologi Indonesia, 2023)
Introduction : Orbital retinoblastoma (RB) is a dire event with a bleak prognosis. This report highlights the severe complications of retinoblastoma resulting from insufficient diagnostic and treatment efforts due to inadequate medical resources and socio-economic challenges. Case Illustration : A 4-year-old boy was brought in with swelling on his left eye socket and jaw, present for two months.He had exhibited leukocoria followed by proptosis 12 months prior and underwent enucleation without dermato-fat graft (DFG) five months ago. Histopathology revealed retinoblastoma without optic nerve invasion. Despite referral to a regional hospital for chemotherapy, he did not receive treatment due to socio-economic constraints. Two months post-operation, the left eye prosthesis spontaneously dislodged, accompanied by an enlarging eye and a left jaw mass. An ophthalmologic assessment disclosed a mass in the left orbital socket, while the right eye appeared normal. A CT scan identified masses in the left orbit, parotid, and masticator spaces, as well as bilateral colli lymphadenopathy. The patient was diagnosed with residual retinoblastoma and received chemotherapy. Discussion : Imaging is crucial in proptosis patients to determine tumor extent and management strategies. The standard approach involves initial chemotherapy, surgery, radiotherapy, and additional chemotherapy. High-risk histological features (HHRF) also warrant chemotherapy, although the presence of such features remains undetermined in this case. Employing multiple treatment modalities may enhance prognosis. Conclusion : Thorough examination and management are essential in retinoblastoma cases. Patient family education and diligent care play a crucial role in preventing the progression and spread of retinoblastoma.